Accountability in the EU's para-regulatory state: The case of the Economic and Monetary Union - Mark Dawson; Adina Maricut-Akbik (Regulation & Governance, 2021)
This article revisits Majone's famous argument about accountability in the regulatory state in reference to the European Union's (EU) Economic and Monetary Union. We show that the EU has entered the stage of a “para-regulatory state” marked by increasing EU regulation in areas linked to core state powers. Despite the redistributive and politicized nature of these policy areas, the EU's “para-regulatory state” has continued to rely on its regulatory model of accountability, focused on decisionmaking processes, and interest mediation. In line with Majone, we describe the model as procedural and contrast it to substantive accountability – which is necessary when regulation has clear redistributive implications. Using two case studies from fiscal policy and monetary affairs, we illustrate the predominance of procedural accountability as exercised by the European Parliament and EU Courts. We complement the empirical analysis with a normative discussion of how substantive accountability could potentially be rendered in both fields.
Keywords: 330; accountability; European Union; Economic and Monetary Union; “para-regulatory state”; regulatory state